Regulation of MT1-MMP/MMP-2/TIMP-2 axis in human placenta - Vincent ZL; Mitchell MD; Ponnampalam AP (Dove Medical Press, 2015)
Zoë L Vincent,1,2 Murray D Mitchell,l,3 Anna P Ponnampalam1,2 1Liggins Institute, 2Gravida: National Centre for Growth and Development, University of Auckland, Auckland, New Zealand; 3University of Queensland Centre for Clinical Research, Brisbane, QLD, Australia Abstract: Matrix metalloproteinases (MMPs) and specific endogenous tissue inhibitors of metalloproteinases (TIMPs) mediate rupture of the fetal membranes in both physiological and pathological conditions. MMPs and TIMPs are subject to regulation by DNA methylation in human malignancies and pre-eclampsia. To determine if membrane type 1 MMP (MT1-MMP), MMP2, and TIMP2 are regulated by DNA methylation in human placentas, we employed an in vitro model where human placental tissues were collected at term gestation and cultured with methylation inhibiting agent 5-aza-2′deoxycytidine (AZA) and lipopolysaccharide. The results suggest that DNA methylation is not directly involved in the regulation of MT1-MMP in placental tissue; however, remodeling of chromatin by a pharmacologic agent such as AZA potentiates an infection-related increase in MT1-MMP. MT1-MMP is a powerful activator of MMP2 and this action, coupled with either no change or a decrease in TIMP2 concentrations, favors a gelatinolytic state leading to extracellular matrix degradation, which could predispose fetal membranes to rupture prematurely during inflammation. Keywords: placenta, epigenetic regulation, DNA methylation, MMPs, labor